Community Structure of Bacillariophyceae Class Microalgaes in Interidal Waters of Gili Sulat, East Lombok - Nadia Audina; Khairuddin Khairuddin; Lalu Japa (Jurnal Biologi Tropis, 2023)
Gili Sulat is a mangrove forest area that is still in good condition and has a role in balancing the surrounding ecosystem, especially for the microalgae community. The community structure of the microalgae (phytoplankton) class Bacillariophyceae of the intertidal ecosystem of Gili Sulat, East Lombok has not been identified. The research was conducted to determine the community structure of the Basillariophyceae class in the Gili Sulat Intertidal Waters, East Lombok. This type of research is descriptive exploratory. Sampling of water in the Intertidal Waters of Gili Sulat, East Lombok, was carried out at six sampling points.  The analytical indices used are the density index, the diversity index, the species evenness index, and the importance value. The total density is 1,745 individuals/liter. The species diversity index value of 2.92 is included in the medium category. The highest significant value was obtained by Synedra ulna of 45.80% and was the species found at each sampling point. The species evenness index of 0.82 is classified as stable (even), meaning that no species dominates the large number of individuals at a particular sampling point. The community structure of the microalgae class Bacillariaphyceae in the intertidal waters of Gili Sulat, East Lombok is quite stable because it has a fairly high density, with species diversity in the moderate category and high evenness of species and the dominance of each species is relatively the same (so no species dominates).